Occupational Exposure and Pterygium Development in an Urban Setting - Alfa Sylvestris; Alif Basor Aminudin Listiawan; Aryani Vindhya Putri (Universitas Muhammadiyah Malang, 2025)
Pterygium prevalence varies globally, with Indonesia demonstrating a high incidence, affecting a notable proportion of individuals bilaterally and unilaterally. Outdoor occupation is a recognized etiological factor, significantly associated with pterygium in Sulawesi, Indonesia, accounting for a large percentage of cases. This study investigated the influence of job-related risk factors on pterygium development in Malang City. Seventy-six participants completed questionnaires, and data were analyzed using appropriate statistical methods. Significant associations were found between several occupational aspects and pterygium presence, including working outdoors, duration of sun exposure, length of employment, and use of protective eyewear. Further analysis revealed that these occupational risk factors substantially impact the likelihood of developing pterygium, increasing the odds by a certain degree. Specifically, prolonged sun exposure, extended work periods, and the absence of UV protection during work were associated with a considerably higher risk. Interestingly, while outdoor work is a risk factor, its impact on the odds of developing the condition appears comparatively smaller than these other factors. In conclusion, job-related risk factors play a significant role in pterygium development in Malang City, with extended sun exposure, long working durations, and the lack of UV protection being the most influential elements, while outdoor work itself presents a less pronounced increase in risk.